Implementation of Tilapia Biofloc Technology in the Bulian Sari Group as an Effort to Reduce Lake Pollution in Pancasari Village, Buleleng, Bali - Sang Ayu Made Putri Suryani; I Made Kawan; I Gede Sudiarta; Agus Surya Pratama; Ni Made Darmadi; Yoga Parawangsa; Mia Freshnido; Hanilyn Hidalgo; Amee Nicolas (PT FORMOSA CENDEKIA GLOBAL, 2023)
Cultivating tilapia in round ponds with the biofloc system which has the advantage that tarpaulin ponds are easy to make, and the pond temperature is more stable than cement ponds. The methods that will be carried out in the implementation of this training are interviews, face-to-face, counseling and direct practice. The advantage of tarpaulin pools is that they are efficient in using water because we only need to fill in water at the beginning and the addition of water is also adjusted according to conditions. The application of Biofloc technology in Pancasari Village can increase tilapia production. The biofloc system can also increase the Survival Rate (SR) of fish and reduce the Feed Conversion Ratio (FCR).